Adaptasi MSLQ untuk Kesuksesan Mahasiswa: Eksplorasi Faktor Motivasi Belajar di Fakultas Ekonomi dan Bisnis Universitas Budi Luhur - Kuncoro, Aris Wahyu; Widyastuti, Umi; Sariwulan, Tuty; Yohana, Corry (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This study aims to analyze the factors that influence Student Learning Motivation. Data collection using online forms with the Census method and the analysis method used is Exploratory Factor Analysis (EFA) with a Research Sample of 238 Students of the Faculty of Economics and Business Class of 2023. Based on the results of this study, 10 factors were obtained that influence student learning motivation, self-confidence factors, self-doubt factors, Intrinsic Motivation, Academic Motivation or Motivation to Learn, Emotions Related to Academic Achievement, Confidence in Academic Ability, Extrinsic and Intrinsic Motivation factors, Self-Confidence in Learning Ability, Knowledge Transfer Confidence. Confidence in Learning Ability. Based on the results of the analysis, it can be concluded that there are 10 factors out of 31 indicators that motivate student learning. Factors that influence students' learning motivation are self-confidence factors, self-doubt factors, Intrinsic Motivation, Academic Motivation or Motivation to Learn, Emotions Related to Academic Achievement, Confidence in Academic Ability factors, Extrinsic and Intrinsic Motivation factors, Self-Confidence in Learning Ability, Confidence Knowledge Transferability. Confidence in Learning Ability.